Unravelling the cellular networks that regulate proteotoxic stress - Varanda, Ana Sofia Paulo Varanda (2017)
Protein synthesis fidelity is essential for proteome stability and for functional maintenance of cellular processes. Errors occur at frequencies around 10-4 under normal physiological conditions and are tolerated by cells. If the frequency of these basal errors increases, the mechanisms of protein quality control become overload, leading to accumulation of misfolded proteins that may aggregate. Several conditions have been associated to this phenomenon, namely aging and neurodegeneration. But, the cause-effect mechanisms remain to be clarified in many cases. In order to elucidate how human cells respond to the accumulation of protein synthesis errors (mistranslation) throughout time, we have developed a methodology that allows for the random serine misincorporation in proteins on a proteome wide scale. The anticodon of a human serine tRNA was mutated to read non-cognate codons. HEK293 cells expressing these tRNAs accumulate ubiquitinated proteins and in some cases protein aggregates. Despite this, only slight alterations in proliferation and viability were detected after several passages in culture. Here we show that activation of quality control pathways, namely molecular chaperones, ubiquitin-proteasome system and unfolded protein response was dependent on the type of amino acid misincorporation. In addition, we observed that evolution of these cell lines in culture deregulates gene expression, for example genes involved in endoplasmic reticulum stress and glycolysis were upregulated. Whole-exome sequencing of evolved cell lines revealed that our cells accumulate a small number of mutations comparatively to the control cell line, in genes involved in transcription and RNA binding. Our data indicate that HEK293 cells adapt to protein synthesis errors mainly through activation of protein quality control mechanisms and other cellular processes depending on the type of amino acid substitution and cells passage number. This study reveals new insights on how human cells adapt to protein synthesis errors and the consequent accumulation of aberrant proteins.